Rancang Bangun Sistem Penjualan dan Inventaris Toko Bangunan XYZ Berbasis Laravel 11 Dan Tailwind CSS Dengan Flowbite - Anggreni, Ayu Desi Relia; Murdika, Pande Made Angga; Yudatama, I Ketut; Putra, I Wayan Edlyn Arsanta; Sanjaya, I Gede Wahyu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The sales and inventory management system at XYZ Building Store often faces numerous problems stemming from manual methods, such as errors in documentation, slow stock report production, and transaction inefficiencies. The waterfall model is best suited for system development in small to medium projects, especially when system requirements are defined from the beginning. Needs evaluation, system design, system development, system feasibility assessment, and system maintanance are elements of the waterfall model. This research intends to create a web-based sales and inventory management platform for the XYZ building store by employing Laravel 11 and Tailwind CSS frameworks, along with the Flowbite template. The Laravel and Tailwind CSS frameworks were chosen for their capability to ease website development and create a sleek, contemporary, and responsive site. The study's results demonstrate that the created system has successfully met user needs and incorporates a modern and flexible design. The results from assessing the system developed through the Black Box Testing method, comprising 6 modules and 12 scenarios, demonstrate a 100% validity rate, which implies that the system functions efficiently and is appropriate for general application.